Otologic Manifestations of Langerhans Cell Histiocytosis: A Systematic Review. (4th May 2021) - Chen, Tiffany; Ashman, Peter E.; Bojrab, Dennis I.; Johnson, Andrew P.; Benson, Brian; Hong, Robert S.; Svider, Peter F.
Abstract : Objective: To perform a systematic review to investigate common otologic manifestations of Langerhans cell histiocytosis, the incidence of these findings, methods for diagnosis, as well as medical and surgical management Data Sources: PubMed/MEDLINE, Embase, and Cochrane Library. Review Methods: A search of PubMed/MEDLINE, Embase, and Cochrane Library for all articles published between 1963 to 2020 was performed with variations and combinations of the following search terms: Langerhans cell histiocytosis, eosinophilic granuloma, Letterer‐Siwe, Hand‐Schüller‐Christian, otitis, otologic, ear. A review of the references of all included articles was also conducted. Results: Sixty‐two articles encompassing 631 patients met inclusion criteria. Otologic symptoms at presentation were found in 246 (39%) patients in the reported studies with 48% reporting bilaterality. The mean age was 14.8 years with a male predominance (64%). The most common otologic presenting symptom was otorrhea (46%). A majority had the multisystem variant (52%). The most common treatment modalities were chemotherapy (52%), followed by surgery (50%), systemic steroids (45%), and radiotherapy (31%). Surgery was performed in 75.8% with unisystem involvement and in 50.6% with multisystem involvement. The most effective treatments included radiotherapy (56% success rate, 17% of treated patients), systemic steroids (44% success, 20% treated), chemotherapy (41% success, 21% treated), and surgical modalities (36% success, 19% treated). Conclusions: Otologic manifestations that occur with the multisystem variant or are at high risk for central nervous system involvement necessitate systemic treatment. For unifocal lesions, surgery is recommended. Lastly, radiotherapy should be reserved for extensive lesions involving vital structures or presenting in older patients.